Impact of Glycopeptide Resistance in Staphylococcus aureus on the Dalbavancin In Vivo Pharmacodynamic Target - Lepak, A. (Antimicrob Agents Chemother, 2015)
Dalbavancin is a novel lipoglycopeptide with activity against Staphylococcus aureus, including glycopeptide-resistant isolates. The in vivo investigation reported here tested the effects of this antibiotic against seven S. aureus isolates with higher MICs, including several vancomycin-intermediate strains. Results of 1-log kill and 2-log kill were achieved against seven and six of the isolates, respectively. The mean free-drug area under the concentration-time curve (fAUC)/MIC values for net stasis, 1-log kill, and 2-log kill were 27.1, 53.3, and 111.1, respectively.